Dowody przejęte do postępowania podatkowego z innych postępowań – perspektywa teoretyczna - Obuchowski, Szymon (Kwartalnik Prawa Podatkowego, 2016)
The paper concerns the possibility which stems from provisions No 180 and 181 of the Tax Ordinance Act, which, taken together enable tax organs to include as evidence in tax proceedings materials assembled in the course of criminal, financial crime and financial misdemeanours trials. Central point of discussion which rose around these rules in tax theory is the question of necessity of repeating the hearing of witnesses, if the tax organ decides to use as evidence in tax proceedings protocols containing their testimonies. Scholars and courts dealing with the question formed several different stances, whose representatives propose different solutions for the problem. With reference to tax and criminal proceedings theory and their output concerning general theory of evidence, as well as legal theory in respect to legal principles theory, Author states, that tax organs may indeed use the witnesses protocols from criminal cases materials without arrangement of additional hearings during the tax proceedings, but it is not possible to give a definite answer to the question posed above judging only from the Tax Ordinance Act, apart from individual circumstances of each case. Answer to the question depends on proper balancing of legal principles which guide detailed rules governing evidence gathering process, and which can be also viewed as making proper use of M. Czubalski’s classification of means of evidence. Taken together they may serve as a methodological answer for the posed problem.